Maternal and neonatal morbidity and mortality among pregnant women with and without COVID-19 infection: the INTERCOVID Multinational Cohort study - Villar, J; Ariff, S; Gunier, RB; Thiruvengadam, R; Rauch, S; Kholin, A; Roggero, P; Prefumo, F; do Vale, MS; Cardona-Perez, JA; Maiz, N; Cetin, I; et al. (Lippincott, Williams and Wilkins, 2022)
At the beginning of the COVID-19 pandemic, the extent of the risks of a COVID infection during pregnancy were unknown. During the start of the pandemic, there were only a few studies published comparing outcomes between pregnant women with and without COVID-19 infections. The INTERGROWTH-21st Consortium conducted a prospective, longitudinal, observational study (INTERCOVID), which assessed the association between COVID-19 and maternal/neonatal outcomes in pregnant women with a COVID-19 diagnosis compared with enrolled pregnant women without a COVID-19 diagnosis. This study enrolled patients from 43 hospitals in 18 different countries between March 2020 and October 2020. As a comparison group, the researchers enrolled 2 unmatched, consecutive, uninfected women immediately after each infected woman was identified, at any stage of pregnancy or delivery, and at the same level of care. Both women and neonates were followed until hospital discharge. COVID-19 was diagnosed by laboratory confirmation and/or radiological pulmonary findings or 2 or more predefined COVID-19 symptoms. The primary outcomes of the study were indices of maternal and severe neonatal/perinatal morbidity and mortality. In all, 706 pregnant women with a COVID-19 diagnosis and 1424 pregnant women without a COVID-19 diagnosis were enrolled. The women had broadly similar demographic characteristics (mean [SD] age, 30.2 [6.1] years). Three hundred twenty-three women were overweight early in pregnancy (48.6%) with COVID-19 diagnosis and 554 women (40.2%) without. Women with COVID-19 diagnosis were more likely to have preeclampsia/eclampsia (relative risk [RR], 1.76; 95% CI, 1.27–2.43), severe infections (RR, 3.38; 95% CI, 1.63–7.01), intensive care unit admission (RR, 5.04; 95% CI, 3.13–8.10), maternal mortality (RR, 22.3; 95% CI, 2.88–172), preterm birth (RR, 1.59; 95% CI, 1.30–1.94), medically indicated preterm birth (RR, 1.97; 95% CI, 1.56–2.51), severe neonatal morbidity index (RR, 2.66; 95% CI, 1.69–4.18), and severe perinatal morbidity and mortality index (RR, 2.14; 95% CI, 1.66–2.75). Women with a fever and shortness of breath were more likely to have severe maternal complications (RR, 2.56; 95% CI, 1.92–3.40) and neonatal complications (RR, 4.97; 95% CI, 2.11–11.69). Women who were asymptomatic with a COVID-19 diagnosis remained at higher risk only for maternal morbidity (RR, 1.24; 95% CI, 1.00–1.54) and preeclampsia (RR, 1.63; 95% CI, 1.01–2.63). Among women who tested positive for COVID-19 (98.1% by real-time polymerase chain reaction), 54 (13%) of their neonates tested positive. Cesarean delivery (RR, 2.15; 95% CI, 1.18–3.91) but not breastfeeding (RR, 1.10; 95% CI, 0.66–1.85) was associated with increased risk for neonatal COVID-19 test positivity. In this study, COVID-19 in pregnancy was associated with consistent and substantial increases in severe maternal morbidity and mortality and neonatal complications compared with pregnant women without a COVID-19 diagnosis. These findings highlight the importance of following the recommended COVID-19 preventative measures.